Rincones lúdicos y su incidencia en el aprendizaje cognitivo de los niños de educación inicial II - Pulecio Martínez, Stephany Elizabeth (2024)
Previous studies on cognitive learning have pointed out the importance of play environments to stimulate the development of cognitive skills in preschool children. In this context, the present research was conducted in the San José Educational Unit, located in the city of Babahoyo, Los Ríos province, which was selected for its representativeness in the subject and access to relevant data. The main objective was to analyze the impact of the play corners on the cognitive learning of students in Early Childhood Education II. A mixed methodology of qualitative and quantitative approach was used, which included a literature review through scientific articles, books, theses, blogs, etc. In addition, data collection was carried out and a questionnaire was developed with structured questions based on the study variables, the questionnaire was addressed to parents and teachers, another key instrument for this research was the observation sheet. The results highlight the relevance of the play corners, evidencing their positive influence on the cognitive development of children. It is concluded that the implementation of these corners is fundamental to enrich the preschool learning process and suggests the need for programs that promote key cognitive skills from an early age.